From the patio to the classroom: experiments to think about the concept of class from the Greek culture (Research, Society and Development, 2022)
This research constitutes one of the elements of the doctoral research under the title "The class as a question and problem: experimentation and criticism", which aims to explain the process of constitution and consolidation of the concept of class over time. This investigation considers elements of qualitative and quantitative research, in a perspective of complementarity. In particular, it is configured from elements of bibliographic. It is worth mentioning that one of the data sources of this investigation was the interview with teachers. We understand that when we think about educational processes, we perceive a convergence towards what we call class. For this reason, we believe it is necessary to discuss this concept in more depth, as well as its historical constitution and its implications for our present time. Throughout this work, we look at Greek culture, and seek the origin of the word class, its unfolding and implications for the constitution of the concept today. When analyzing the data collected through interviews with the 16 teachers, we realized that, when thinking about the concept of class, we tend to think of this concept with the meanings of teaching and learning.